Dieta, dinâmica populacional e ectoparasitas de Phrynops geoffroanus (Schweigger, 1812) (Testudinata, Chelidae) do Baixo São Francisco, Poço Redondo, SE - Santana, Daniel Oliveira (2012)
Population of P. geoffroanus of Unidade Unidade de Conservação Estadual Monumento Natural Grota do Angico (MNGA) (37°40 W; 09°39 S) was studied in relation of their diet, morphometry, growth rates and mass gain, structure and dynamic population and parasites (leeches). The sampling of specimens was performed in monthly campaigns over a year (between January and December 2011) through active search between 07:00 and 13:00h, using snorkeling. Regarding diet was recognized 32 categories of food items. The pray with higher index of relative importance were of family Baetidae revealing a weak relationship between abundance of pray in environment and diet of tortoise composition and a high electivity of few catgegories of food items by specie. The indice of electivity (E) varied for different situations studied (e.g. size, sex, seasons). The macroinvertebrate community available in the environment showed subtle fluctuations between sesons (dry and wet). Males and females didn t differ in size, but presented distinct form. As for the mass, males and females did not show significatives differences. The young had higher average growth rate, almost double compared with adults (males and females). Census indicate the presence of at least 77 individuals on population. The overall sex ratio showed a higher shift in favor of males. The population estructure, we could notice the presence of individuals in all size classes, with predominance of adult males. Of the 77 catches of P. geoffroanus performed showed the presence of parasites in 67 (87%). With relation to recaputered animals, of 28 record, 26 (92,8%) presented re-infestation. The parasites observed were leeches of family Glossiphoniidae represente by three morphotypes. There were no differences in the numbers of leeches that parasited juveniles, males and females and neither relationship between body size of turtles and levels of infestation. Regarding the placement of these parasite, leeches were more frequent in the groin, probably because these places presented thinner coat, favorable to the establishment, protection against possible friction during displacement in aquatic environment and against desiccation during periods of assoalhament. Apart from leeches, were observed andoparasites (nematodes) from the samples of stomach contents and also platelminthes (Monogenea; Polystomatidae), which were lodged in oral and pharynx cavity, were fixated across multiple suckers.